Executive Compensation and Insurance Sector Performance: Evidence from Nigeria - Omoregie, Osaretin Kayode; Kelikume, Ikechukwu (International Journal of Economics and Financial Issues, 2019)
This study investigates how six different measures of firm performance affect executive compensation in Nigerian insurance sector (2011-2016). The Im, Pesaran and Shin (IPS) and Kao Residual tests were employed to ascertain stationarity and cointegration of the variables. Mixed stationary and no cointegration were observed. The results indicate that profitability variables (return on asset, return on equity and net profit margin) are insignificant to executive compensation while efficiency variables are significant to executive compensation. That is profitability variables does not have significant effect on executive compensation while corporate performance measured by efficiency variables have effect on executive compensation. It is recommended that the board should focus on efficiency measures in setting executive compensation levels as these ultimately drive profitability and corporate performance in the insurance sector. This study make a meaningful contribution to the literature as very little work has been done in this area. Keywords: Executive Compensation, Insurance Sector Performance, Solvency Ratio, Combined Operating Ratio, Loss Ratio JEL Classifications: J31; J32; J33; M53 DOI: https://doi.org/10.32479/ijefi.7577